THE CORRELATION BETWEEN SELF-EFFICACY AND SPEAKING SKILL OF THE SEVENTH-GRADE IN JUNIOR HIGH SCHOOL - Ni Putu Milla Supita Sari; Luh Ketut Sri Widhiasih; Ni Luh Putu Dian Sawitri (Academic Journal on English Studies (AJOES), 2023)
The present study which made use of an ex-post facto research with correlation design was intended to figure out the significant correlation between self-efficacy and speaking skill of the seventh-grade students of SMPN 4 Denpasar in the academic year 2023/2024. The samples of the research consisted of 54 students which were chosen by means of random sampling method with lottery system. The data were collected through administering the research instruments which were in the form of structured questionnaire and picture description. The obtained data were statistically analyzed by using Pearson product moment correlation and t-test. The results of the data analysis clearly revealed the alternative hypothesis was accepted. In other words, the research findings confirmed that there is significant correlation between self-efficacy and speaking skill of the seventh-grade students of SMPN 4 Denpasar in the academic year 2023/2024.